Anatomical measurement of the ossicles in patients with congenital aural atresia and stenosis. (October 2017) - Li, Jieying; Chen, Keguang; Li, Chenlong; Yin, Dongming; Zhang, Tianyu; Dai, Peidong
Abstract: Objectives: Our aims were to measure and compare anatomical parameters of the ossicles in normal, congenital aural stenosis (CAS), and congenital aural atresia (CAA) ears. Methods: This retrospective study was performed using three-dimensional reconstructed images derived from computed tomography scans of 20 normal subjects, 20 CAS patients, and 20 CAA patients. Results: The lengths of the malleus handle and long process of the incus were greater in normal ears than in CAS and CAA ears (all P < 0.05). The angles of the incudostapedial joint and between the short and long processes of the incus were smaller in normal ears than in CAS and CAA ears (all P < 0.05). There were no significant differences in the positions of the malleus head and incudomalleolar joint, the size of the malleus head, the length of the short process of the incus, or the angle of the incudomalleolar joint (P > 0.05). Conclusions: Anatomical parameters of the lower part, but not of the upper part, of the ossicular chain in CAS and CAA ears differed from those in normal ears. Different branchial arch origins of the upper and lower parts of the ossicular chain may explain these findings. Dysplasia of the second arch, which develops into the lower part of the ossicular chain, may contribute to ossicular malformation in CAA and CAS. Accurate radiographic measurement of malformed ossicles may be useful for reconstructive surgery of CAA and CAS using the patient's native ossicular chain and for choosing an appropriate place for active middle ear implants.